Beliefs about the Gender Gap in Salary Negotiations - Francesco Capozza (CESifo GmbH, 2024)
This paper investigates beliefs concerning the gender gap in salary negotiations (GGSN) in a sample of 4,300 women, 1,000 men, and 105 HR managers residing in the U.S. The respondents believe in the existence of the GGSN, yet they misperceive its magnitude. Providing respondents with accurate information changes their beliefs about it. However, this does not lead to either an increased demand to join a salary negotiation course or a higher willingness-to-pay to get salary information. The analysis of the competing mental models that women hold reveals that the likely mechanism is the perceived backlash that they may experience from employers if they engage in salary negotiations. Finally, a survey of HR managers suggests that they view negotiating women as facing worse consequences in the workplace than negotiating men.
Keywords: C93; D83; D91; J16; M52; 330; beliefs; mental models; perceived backlash; negotiation; gender